Effect of excess lead oxide on phase transitions and physical properties of provskite lead barium zirconate ceramics - Bongkarn T. (2014)
Effect of excess PbO on phase transitions and physical properties of perovskite (Pb0.90Ba0.10)ZrO3 ceramics have been investigated. The (Pb0.90Ba0.10)ZrO3 ceramics were prepared via the conventional mixed oxide method. Excess PbO (1, 3, 5, and 10wt%) was introduced prior to powder calcination. The phase formation and phase transition of (Pb0.90Ba0.10)ZrO3 ceramics were characterized by X-ray diffraction and thermal analysis. The result indicated that excess PbO showed an effect on antiferroelectric to ferroelectric phase transition. However, it was not found significant effect of excess PbO on ferroelectric to paraelectric transition temperature.